Analisis Incident Management E-Court Pada Pengadilan Negeri Salatiga Menggunakan Framework ITIL V4 - Jessica Adelila Ayuh; Hanna Prillysca Chernovita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
In the IS IT organization is the most important part in service activities and smooth business operational activities, PN Salatiga uses the E-Court application from the Supreme Court which functions as a community service forum for case handling, namely case registration (e-filing), online advance payment (e -Payment), electronic summons (e-Summons) and electronic trials (e-Litigation). at Salatiga District Court in handling that still do not use the references used to manage disasters, so the settlement process does not run optimally. If there is an E-Court incident, it will have an impact on service satisfaction for users. This requires incident management with optimal management in accordance with incident standards. The framework used is ITIL V4 with the main components being a service value system and 4 dimensions, the fourth dimension is the value flow and the process which allows the value stream to have an overview for continuous improvement. The research method uses a qualitative approach that can make it easier to see the condition of incident management at Salatiga District Court. This study aims to see and see the handling of the Salatiga PN incident in the management of the ITIL V4 incident. Describe how incident handling is implemented with incident management at ITIL. Incident management SOPs prepared and can be used to support management services at the Salatiga District Court.